The long-QT syndrome: A silent killer - Crowley, Claire (Trinity Student Medical Journal, 2010)
Introduction: Sudden cardiac death is a striking phenomenon, affecting seemingly healthy individuals without warning. The long-QT syndrome is a common cause of sudden cardiac death that can either be inherited or acquired. While congenital long-QT syndrome comprises a heterogeneous group of hereditary disorders affecting ion channels in the heart, acquired long-QT syndrome is usually a result of pharmacological therapy. Main Body: Various mutations in twelve different genes have been linked with the long-QT syndrome to date. This condition is characterised by a pro-longed QT-interval on ECG, which signifies a delay in ventricular repolarisation. The clinical presentation of this syndrome can range from symptoms of dizziness and syncope to sudden death. Diagnosing long-QT syndrome is difficult due to variable penetrance in its inheritance and the existence of yet unidentified causative mutations. Discussion and Conclusions: Accurate diagnosis of the long-QT syndrome is essential as this condition may predispose an individual to sudden cardiac death. Prophylactic therapy for the syndrome exists and therefore early identification of those at risk is crucial in reducing the number of preventable cardiac deaths. Research must continue to discover all mutations re- sponsible for sudden cardiac death so that therapeutic strategies can be developed to combat this silent killer.